Investigating the effect of sense of security and perceived value on tourists\' spatial attachment Case Study (Zanjan Province) - Narges Mousavi; Homa doroudi; Somayeh Moghaddam (تحقیقات کاربردی علوم جغرافیایی)
This study was designed to investigate the impact of perceived security and perceived value on tourists' spatial attachment. The present study is of applied purpose and of descriptive-analytical method. Libraries and field methods were used to collect the required data and data. The statistical population of the study consisted of tourists coming to Zanjan province. The sample size of the study was estimated to be 384 people using Cochran formula. The reliability of the questionnaire was measured by Cronbach's alpha and the combined reliability coefficient (Cr). The validity of the questionnaire was confirmed by face and expert validity and divergent validity by calculating the mean variance index. SPSS and LISREL were used for data analysis. The results showed that the sense of security and perceived value had a significant and positive effect on tourists' spatial attachment.